A Qualitative Study Exploring The Construct Of Student Well-Being In West Java High School Students - Dalimunthe, Karolina Lamtiur; Susanto, Hery; Wedyaswari, Miryam (UI Scholars Hub, 2022)
Student well-being has become a significant goal and outcome of quality education. The “PROSPER (Positivity, Relationships, Outcomes, Strengths, Purpose, Engagement, Resilience) student well-being” is a framework that provides a holistic approach to improve student’s well-being. This study aimed to explore the construct of student well-being in the West Java high school population, based on the PROSPER framework. We focused on exploring high school students in urban areas. A qualitative study was conducted in three different language zones in West Java by using observations and interviews. The data were collected by six enumerators with a total of 108 students using a sequential approach thematic analysis. The study found that student well-being and its components were consistent with the framework. However, we proposed the subcomponents of student well-being and its definitions that reflect the unique characteristics of the population. The study also found that personal factors, social factors, and physical urban environments may influence well-being from students' perspectives. This study suggests that the PROSPER framework can be used to describe student well-being and also guides the government to develop educational policies and intervention programs at school.